Complete remission in an advanced hepatocellular carcinoma patient with AXIN1 mutation after systemic therapy: A case report - Yihong Ran; Xiaozhun Huang; Xu Che; Dong Chen (Heliyon)
Primary hepatocellular carcinoma (HCC) is a common malignancy with high morbidity and mortality. Despite progress in systemic therapies, survival in advanced HCC remains poor due to patient heterogeneity and individual differences, necessitating a personalized approach rather than relying solely on guidelines. Here, we present an exceptional case study in which a systematic regimen without immune checkpoint inhibitors was chosen based on the patient's specific genetic test results. Remarkably effective with long-term survival benefits were observed as a result. This case underscores the importance of incorporating tumor profiling and personalized treatment plans, in addition to adhering to guidelines and standards, for delivering more efficacious and well-tolerated therapeutic options to patients with liver cancer.